What Happens to Graduates? Contrasting Views of Two Systems - Adelman, Clifford (International Higher Education, 2017)
Two surveys of college graduates in large higher education systems, the U.S. and Europe, are presented in terms of their purposes, structural differences, thematic variations, and divergences. The U.S. system has been operating since 1993; the European Graduate Survey is, at present, only a design, completed in 2016. Both are necessary for system accountability and student guidance.